Pengaruh Motivasi, Pengembangan Karir, Kesehatan dan Keselamatan Kerja Terhadap Kinerja Pegawai Pada Badan Pengelola Keuangan dan Aset Daerah Kabupaten Labuhanbatu - Rubiati Ningrum; Yuniman Zebua; Syukron Arjuna (CV. Ulil Albab Corp, 2024)
The purpose of this research is to determine the influence of motivation, career development, and occupational health and safety on the Regional Financial and Asset Management Agency of Labuhanbatu Regency. The population in this study were 42 employees of the Labuhanbatu Regency Regional Financial and Asset Management Agency. And the sample of this study is the entire population. The research results show that it is known that motivation has a positive and significant influence on employee performance. The research results also show that career development has a positive and significant influence on employee performance. The research results also show that occupational health and safety has a positive and significant influence on employee performance.